“Uso de cobertura muerta para el control de malezas en el cultivo de tomate (lycopersicum esculentum) en Lamas-San Martín” - García Navarro, Lita (2006)
The present work has as title "USO DE COBERTURA MUERTA PARA EL CONTROL DE MALEZA EN EL CULTIVO DE TOMATE (Lycopersicon esculentum) EN LAMAS - SAN MARTIN". Likewise with the objective Determining the perks of the vegetable- coverage died utilization in the weeds control in the tomato cultivation in Lamas - St. Martín and determining the treatments's economic analysis. Segundo Najar Najar Accomplished the present work in the lord's piece of land himself, once was located in the Sector Shupishiña, slimes Distrito, Lamas's Provincia.; With a T. The Diseno of Bloques Completa Randomizado (DBCR), with 4 treatments and 4 repetitions Was utilized. T1 (paja de arroz), T2 (hoja de plátano), T3 (cascarilla de arroz) T 4 were treatments {testigo . aftermaths demonstrated than the bigger fruits performances in kiloes for hectare the T3 (cascarilla de arroz), T1 (paja de arroz) and the T2 (hoja de plátano) with 21958,33, 21946.67 and 21875,50 obtained fruit kiloes for hectare respectively, with 4065.32, 3944,02 and 3941,52 net utility new suns and the the T4 went with (testigo) 21687,50 of younger performance fruits kiloes for hectare with 3692,67's net utility new suns.